On problems of systematization of coats on medical products - Filipenko, Volodymyr; Sevidova, Katerina; Timchenko, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article examines principles for systematization of functional-protective coats on medical products and instruments. It is suggested to systematize these coats by several main signs: designation, methods of formation, materials, structure and character of interaction with tissues of the organism. The conducted ranging analysis of the coats, which are known or have prospects to be applied in medicine, will be useful for specialists in medical material science, surgeons, designers of new instruments and implants.